ESG and corporate financial performance: evidence from JSE listed firms - Muzanya, Shelton (Department of Finance and Tax, 2023)
Business is an incredible social construct of the world, consisting of firms that are part of and arise from society. However, businesses have come under increasing scrutiny from internal and external stakeholders over sustainable business practices. A sustainable business model creates a balance between integrity, equity and financial prosperity, the so-called triple-bottom-line. Environmental, social and governance issues (ESG) have become the modern-day proxy for sustainable business practices. The relationship between sustainable business practices and corporate financial performance is a relatively new but prominent area of research in practice and academia in South Africa. This study explores the relationship between ESG disclosure performance and the corresponding corporate financial performance (CFP) for 70 sampled firms listed on the Johannesburg Stock Exchange (JSE) between the periods 2011 and 2019. In line with international and South African research, ESG in its composite and disaggregated form was considered against a select number of CFP metrics. Select accounting-, market- and qualitybased CFP metrics were considered. Quantitative research methods were employed, using panel regression models to investigate the ESG-CFP relationship where ESG was the independent variable while the CFP metrics were individually considered as the dependent variables. All CFP data was obtained from Bloomberg and Bloomberg's proprietary ESG scores were used. This study finds a statistically significant negative relationship between ESG and the selected CFP metrics. Upon disaggregating the ESG scores, it was evident that the E- and S-scores were also significantly and negatively related to the CFP metrics whilst the G-score was positively related to CFP, but it was not statistically significant. The empirical evidence suggests that over a nine-year investment horizon, higher ESG disclosure performance detracts from firm fundamental and market performance. Further interpretation of the results in conjunction with the literature may suggest that ESG ought to be seen as an insurance policy against excessive underperformance during volatile periods and not a CFP enhancer. Therefore, being “over-insured with ESG” may lead to underperformance.